2017
DOI: 10.1080/21501203.2017.1383319
|View full text |Cite
|
Sign up to set email alerts
|

Identification and determination of myriocin in Isaria cicadae and its allies by LTQ-Orbitrap-HRMS

Abstract: A hybrid linear ion trap-quadrupole-Orbitrap high-resolution mass spectrometry (LTQ-Orbitrap-HRMS) was used to qualitatively and quantitatively analyse the myriocin in Isaria cicadae and its allies. The samples were prepared with 95% methanol for 30 min by ultrasonic-assisted extraction. The target compound was purified by ODS solid-phase extraction (SPE) column. The enriched samples were identified by mass spectrometry. The results showed that the contents of myriocin in both wild and artificial Isaria cicada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The two authoritative fungal taxonomy databases, Mycobank (http://www.mycobank.org/) and Species Fungorum (http://www.indexfungorum.org/), however, both accept I. cicadae and treat C. cicadae as a synonym of I. cicadae . A recent study suggested that C. cicadae may be different from I. cicadae since they showed difference in myriocin contents (Cheng et al ., ). In addition, in response to the ending of dual nomenclatural systems for pleomorphic fungi, a molecular phylogenetic investigation proposed names that should be maintained and names that should be rejected in Cordycipitaceae (Kepler et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The two authoritative fungal taxonomy databases, Mycobank (http://www.mycobank.org/) and Species Fungorum (http://www.indexfungorum.org/), however, both accept I. cicadae and treat C. cicadae as a synonym of I. cicadae . A recent study suggested that C. cicadae may be different from I. cicadae since they showed difference in myriocin contents (Cheng et al ., ). In addition, in response to the ending of dual nomenclatural systems for pleomorphic fungi, a molecular phylogenetic investigation proposed names that should be maintained and names that should be rejected in Cordycipitaceae (Kepler et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This α-amino fatty acid derived product is isolated from several genera of fungi, mostly by Myriococcum , 316 Melanconis 317 and Isaria . 318 It inhibits sphingosine biosynthesis by blocking the activity of serine palmitoyltransferase, which is a potent immunosuppressant with 10- to 100-fold more activity than that of immunosuppressant 94 . 319,320 It further served as the leading structure of fingolimod, which was approved by the FDA and became the first oral drug available for the treatment of relapsing–remitting forms of multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Myriocin was extracted from Cordyceps using a similar protocol described before 71 . Briefly, extraction of myriocin was performed by weighing 0.5 g of dried Cordyceps powder which was then sonicated with 95% methanol (MeOH) (3 × 10 mL) for 40 min at 40 °C.…”
Section: Methodsmentioning
confidence: 99%